THE USE OF CHARADE GAME TO TEACH VOCABULARY (An Experimental Study of the Seventh Graders of MTs. Miftahul Khoirot Branjang in the Academic Year of 2014/2015) (ELT Forum: Journal of English Language Teaching, 2016)
This article is about the use of charade game to teach vocabulary in the seventh graders of MTs. Miftahul Khoirot Branjang in the academic year of 2014/2015. This research is conducted by using quasi-experimental design. The population is all seventh graders of MTs. Miftahul Khoirot Branjang in the academic year of 2014/2015. The researcher chooses 54 students from two classes as the sample of the study, 27 students as experimental groups and 27 students as control group. In the pre-test, the average score of experimental group is 59.70 and the average score of control group is 57.63. Then, the experimental group is taught by using charade game whereas the control group is taught by using conventional method. The results from post-tests show that the average score of experimental group is 87.26 whereas the average score of the control group is 79.26. After calculating by t-test, the result of the t-value is 3.05 and t-table is 2.006. The t-value of the post test is higher than the critical value means that statistically there is significant difference between two groups. Since the experimental group gets higher average scores (87.26 > 79.26), it can be concluded that teaching vocabulary using charade game results better achievement.